Mental Health and Functioning in School Age Children of Female Entertainment Workers in Cambodia - Ean, Nil; Pollack, Amie Alley; Ngoc, Do Khanh (VNU Journal of Science: Education Research, 2019)
Globally, approximately 10% - 20% of children and adolescents experience mental health problems and the majority of them are living in low- and middle-income countries. Children of female sex workers are often exposed to unsafe environments, traumatic experiences and a mentally ill parent, putting them at risk for developing mental health problems themselves. Research on the mental health and functioning of children of female sex workers during their school age is limited. This paper will explore the mental health and functioning of female sex workers’ children. Method: The study included 160 female entertainment workers (FEWs) and 60 of their children from four provinces of Cambodia. FEW’s mental health, and children’s mental health and functioning were measured. Result: FEWs demonstrated high rates of depression (67%) and anxiety (61%), and 54.38% reported symptoms of post-traumatic stress disorder. Of the 60 children, the majority got their education at primary school (68%) and secondary school (25%). 46.7% of them reported symptoms of functional impairment, 18.33% suffered from psychological distress, and 36.67% have PTSD symptoms above the clinical threshold. Children’s psychological distress was significantly predicted by mothers’ early childhood traumatic experiences, mothers’ current mental health problems, mothers’ anxiety and PTSD. Mother’s PTSD predicted children’s psychological distress [β = 0.282, R 2  = 0.079] and functioning [β = 0.285, R 2  = 0.081]. Conclusion: School age children of FEWs have high rates of depression, anxiety and PTSD. Children’s psychological problems impair their functioning at school and home. FEW’s PTSD predicts their children’s psychological distress and functioning. Further research on the mental health and functioning of FEW’s children should be continued with a larger sample size. Mental health professionals and educators should provide mental health care for FEWs and their children, and develop evidence-based approaches to improving children’s mental health and functioning